2020
DOI: 10.35772/ghm.2020.01018
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care for patients with COVID-19 on extracorporeal membrane oxygenation (ECMO) support

Abstract: In Japan, four medical facilities including our own -the National Center for Global health and Medicine (NCGM) -have been designated for the treatment of specified infectious diseases by the Minister of Health, Labour, and Welfare. Here, we report our nursing care for patients with severe COVID-19 on extracorporeal membrane oxygenation (ECMO) support. In addition to infection control measures in the form of an N95 mask, a water-repellent isolation gown, a cap, a shielded mask on top of the N95, and double-laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
(9 reference statements)
0
21
0
Order By: Relevance
“…The WHO provides a guide for both prevention and protection. Studies demonstrated that for performing aerosol-generating procedures, the proper level of PPE includes a respirator, eye protection goggles, a gown with long sleeves, and a full-length apron [7,8,20,25]. The correct use of PPE by healthcare professionals for COVID -19 is key for limiting the spread of infection.…”
Section: Appropriate Level Of Ppementioning
confidence: 99%
See 4 more Smart Citations
“…The WHO provides a guide for both prevention and protection. Studies demonstrated that for performing aerosol-generating procedures, the proper level of PPE includes a respirator, eye protection goggles, a gown with long sleeves, and a full-length apron [7,8,20,25]. The correct use of PPE by healthcare professionals for COVID -19 is key for limiting the spread of infection.…”
Section: Appropriate Level Of Ppementioning
confidence: 99%
“…Our simulation has demonstrated two key factors important for the management of patients with COVID-19, the ability to properly communicate and strategically minimize the number of clinicians in the patient's room. The balance between providing an e cient therapy and safety of personnel requires strict control with PPE, compliance with respecting the hot and cold zones [8], and adherence to standards of involving only the necessary number of clinicians in the isolation room [20,26].…”
Section: Critical Care In An Isolation Roommentioning
confidence: 99%
See 3 more Smart Citations